2011
DOI: 10.1371/journal.ppat.1002385
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Transcriptional Regulators Are Essential for Infection-related Morphogenesis and Pathogenicity of the Rice Blast Fungus Magnaporthe oryzae

Abstract: The cyclic AMP-dependent protein kinase A signaling pathway plays a major role in regulating plant infection by the rice blast fungus Magnaporthe oryzae. Here, we report the identification of two novel genes, MoSOM1 and MoCDTF1, which were discovered in an insertional mutagenesis screen for non-pathogenic mutants of M. oryzae. MoSOM1 or MoCDTF1 are both necessary for development of spores and appressoria by M. oryzae and play roles in cell wall differentiation, regulating melanin pigmentation and cell surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 82 publications
2
88
0
Order By: Relevance
“…For instance, MoSOM 1 which is a transcription factor serves as a phosphorylation target for CpkA along the cAMP/PKA pathway in M. oryzae . The physical interaction between MoSom1 and CpkA occurs in the presence of cAMP (Yan et al 2011). MoSom1 also interacts with two other transcription factors namely MoCdtf1 and MoStu1 to regulate appressorium initiation and turgor generation and pathogenesis of M. oryzae .…”
Section: Transcriptional Factors Regulating Appressorium Formation Anmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, MoSOM 1 which is a transcription factor serves as a phosphorylation target for CpkA along the cAMP/PKA pathway in M. oryzae . The physical interaction between MoSom1 and CpkA occurs in the presence of cAMP (Yan et al 2011). MoSom1 also interacts with two other transcription factors namely MoCdtf1 and MoStu1 to regulate appressorium initiation and turgor generation and pathogenesis of M. oryzae .…”
Section: Transcriptional Factors Regulating Appressorium Formation Anmentioning
confidence: 99%
“…MoSom1 also interacts with two other transcription factors namely MoCdtf1 and MoStu1 to regulate appressorium initiation and turgor generation and pathogenesis of M. oryzae . More so, MoCDTF1, MoSOM1 and MoMSB2 are also involved in the regulation of sporulation and development of functional appressorium in M. oryzae (Yan et al 2011). Subsequently, ∆ mosom 1 and ∆ mocdtf 1 strains were non-pathogenic and failed to induce lesions on both susceptible rice and barley seedlings (Yan et al 2011).…”
Section: Transcriptional Factors Regulating Appressorium Formation Anmentioning
confidence: 99%
See 1 more Smart Citation
“…A yeast two hybrid assay identified seven proteins that interact directly with CpkA (15). Recently, the expression of two transcriptional regulators, CDTF1 and SOM1, was reported to be reduced in mac1 and cpkA mutants with Som1 also being shown to interact weakly with CpkA (16). Mutational analysis of these two genes indicated that each has multiple pleiotrophic effects on growth and development in M. oryzae (16).…”
mentioning
confidence: 99%
“…Recently, the expression of two transcriptional regulators, CDTF1 and SOM1, was reported to be reduced in mac1 and cpkA mutants with Som1 also being shown to interact weakly with CpkA (16). Mutational analysis of these two genes indicated that each has multiple pleiotrophic effects on growth and development in M. oryzae (16). Furthermore, a total of 110 cAMP responsive sequence tags were identified in a SAGE analysis of conidia following cAMP treatment of which 60 (50 up-regulated and 10 down-regulated) were assigned to a gene or expressed sequence tag (17).…”
mentioning
confidence: 99%